The Oostvaardersplassen as a key moulting site for Greylag Geese Anser anser in western Europe - Zijlstra, Menno; Loonen, Maarten J J E; van Eerden, Mennobart R; Dubbeldam, Wouter (Wildfowl, 1991)
Since its formation in 1968, the Oostvaardersplassen has become the largest moulting site for Greylag Geese in western Europe. In recent years, over 30,000 non-breeding geese have been counted in the area. Geese breeding in the former German Democratic Republic (GDR) are observed most frequently during moult, while birds from Norway form the majority of colour-marked individuals in autumn and spring. The absence of moulting Norwegian Greylags is thought to be due to a difference in the timing of moult in geese belonging to different breeding grounds. This idea is based on a positive relation between arrival of moult in two successive years, a difference in day of arrival for geese from Sweden and the GDR, and a trend in mean hatching date with latitude. During moult, the Oostvaardersplassen is visited by geese ranging from 1 to 14 years. Improved data on the mortality rate of geese from the GDR are essential to study the relative abundance of geese from different age classes in the moulting flock.